THE RELATIONSHIP BETWEEN KNOWLEDGE AND MOTIVATION IN HYPERTENSION SELF-MANAGEMENT WITH BLOOD PRESSURE IN HYPERTENSIVE PATIENTS - Asmoro, Candra Panji; Sriyono, Sriyono; Maharani, Clarita (Universitas Nahdlatul Ulama Surabaya, 2025)
Introduction: The trend of increasing hypertension tends to increase and shift to a younger age. Self-management of hypertension is a strategy to help individuals with hypertension change their negative behaviour. The application of hypertension self-management is influenced by predisposing factors such as the level of knowledge and motivation. Objective: This study aimed to analyse the relationship between knowledge and motivation in hypertension self-management with the blood pressure of hypertensive patients. Methods: This study used a correlational study with a cross-sectional approach. Respondents in this study were 146 hypertensive patients who were recruited using the purposive sampling technique. The independent variables in this study were the level of knowledge and motivation in hypertension self-management. The dependent variable in this study was blood pressure. The instruments used were questionnaires and blood pressure observation sheets. Analysis used Kendall’s tau-b statistical test with a significance value of p < 0.05. Results: The results of this study are the relationship between the level of knowledge (p=0.000, r=-0.591) and motivation in hypertension self-management (p=0.000, r=-0.601) with blood pressure. Conclusions: Patients with hypertension correlate with their blood pressure and their level of motivation and knowledge about self-management of their condition. The level of knowledge and motivation is an important value that can help them achieve a more normal blood pressure value.